2016
DOI: 10.1111/jsap.12428
|View full text |Cite
|
Sign up to set email alerts
|

Facial and vestibular neuropathy of unknown origin in 16 dogs

Abstract: Facial and vestibular neuropathy of unknown origin shares similarities with idiopathic facial paralysis. The prognosis for return of normal facial and vestibular function is guarded and there may be relapse after recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 30 publications
10
38
0
Order By: Relevance
“…The oculomotor parasympathetic axons are located superficially on the medial side of CN III, subsequently if the neuropathy initiates in this location it is likely that only the parasympathetic component will be affected. The clinical signs were unilateral in all dogs in this study, similar to the reported canine cases of idiopathic facial neuropathy but different to trigeminal neuropathy . There are several cases published of unilateral idiopathic trigeminal neuropathy in dogs, however the majority are bilaterally affected .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The oculomotor parasympathetic axons are located superficially on the medial side of CN III, subsequently if the neuropathy initiates in this location it is likely that only the parasympathetic component will be affected. The clinical signs were unilateral in all dogs in this study, similar to the reported canine cases of idiopathic facial neuropathy but different to trigeminal neuropathy . There are several cases published of unilateral idiopathic trigeminal neuropathy in dogs, however the majority are bilaterally affected .…”
Section: Discussionsupporting
confidence: 84%
“…The mean recovery time of motor function was 5 weeks in the present study, similar to other idiopathic cranial neuropathies; however, a third of the cases affected with CN III motor dysfunction (4/11 dogs) in our study showed no signs of improvement. This finding differs from trigeminal neuropathy where the motor function recovered in all cases; but similar to facial neuropathy, where resolution of clinical signs was only seen in half of the affected dogs . Some degree of mydriasis persisted in all cases in our study; however, almost a quarter of patients recovered partial CN III parasympathetic function.…”
Section: Discussionmentioning
confidence: 99%
“…PVD combined with facial nerve deficits was presumably induced by idiopathic conditions in the current study population. In other studies similar findings of concurrent facial nerve palsy with idiopathic vestibular syndrome were described and different hypotheses were discussed (Garosi et al 2001, Jeandel et al 2016. Underlying inner ear disease could possibly not be detected using MRI if lesions were very small (Garosi et al 2001) or early stages of inflammatory disease might also be overlooked (Jeandel et al 2016).…”
Section: Discussionmentioning
confidence: 78%
“…, Jeandel et al . ). Underlying inner ear disease could possibly not be detected using MRI if lesions were very small (Garosi et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation